Emergency Remote Teaching amidst Global Pandemic: Voices of Indonesian EFL Teachers - Arif Nugroho; Mariam Haghegh; Yunika Triana (VELES Voices of English Language Education Society, 2021)
A number of research studies have been conducted to examine the practices and challenges of online English language teaching in the age of Covid-19 pandemic. However, research on the teachers’ insights and suggestions to overcome the challenges of the emergency remote teaching still remains unexplored. The present study shed some light on EFL teachers’ teaching activities, challenges, and insights of the emergency remote teaching amidst the global pandemic. The data were obtained from 27 Indonesian EFL teachers (17 female and 10 male) by means of self-written reflection and semi-structured interview. The results revealed that the emergency remote teaching activities were conducted by administering online forum and discussion, integrating social media, and designing interactive exercises. Notwithstanding the facts, the teachers encountered some challenges such as unfamiliarity with digital platforms, inability to provide quick feedbacks, and lack of students’ motivation and engagement during the remote teaching. In responding to the challenges, this study further depicted that joining professional development programs, creating representative lesson plan, and designing interactive online classroom activities could became alternative solution. These results contribute to the realm of English language teaching as fruitful insights and as a ‘wake-up call’ for educational stakeholders in order to enhance the efficacy of online teaching and learning, particularly during the global pandemic.